5 - Intricate Entanglement: The ICC and the Pursuit of Peace, Reconciliation and Justice in Libya, Guinea, and Mali - Grovogui, Siba N. (Africa Development, 2021)
International justice is not merely a function of legislation and adjudication. It depends on the extent to which it is viewed as legitimate by litigants and others based on perceptions of the relationships of the operations of existing regimes of dispensation of justice. This is a reflection of the operations of the institutions of justice and those of the international order: including but not limited to the actions of judicial authorities and other judicial auxiliaries and intermediaries who give effect to justice through their interpretation and application of the law. From this perspective, justice extends beyond the ability of courts to specify the legal, material and moral dimensions of an offence. International justice has social ends that are easily undermined by self-interested attempts to delegitimize judicial institutions – a charge often levelled at the African Union – but also by the desire of others to preserve, as a matter of political inherency, their own sovereign spaces. Above all, the social ends of social justice, which is the end of international justice, is undermined by elevating judicial or punitive justice over larger social goals – as the examples in this article suggest.